A new approach to hide texts into images and audio files using steganography and cryptography techniques - Miran Hikmat Mohammed (International Journal of Advances in Applied Sciences, 2022)
These days there are many security issues facing users while they are using the internet for exchanging information among them. And, users use technology devices, such as mobiles and computers, and they connect them to the network and internet. Therefore, users always looking for a safe way to exchange information locally and globally, when they are connecting to a network. Also, these problems lead them to many further issues such as losing privacy, hacking, and detecting personal information. Although, many security techniques have been used to solve these issues by creating many different software utilities; some of them worked perfectly to some extent, while some others still did not comply with the security environment. This research paper finds a new methodology to secure text information while exchanging among permitted users over the internet. This method is a combination of cryptography and steganography with audio and imaging multimedia, which works on hiding and encrypting information before sending it over a network. As result, this technique will add additional security processes to the data exchange, and it will provide a more reliable environment for the user to connect to the network. In addition, the quality of the data will not be altered or noticed during the encryption and decryption process.